Planar all-solid-state rechargeable Zn–air batteries for compact wearable energy storage. Issue 29 (11th July 2019) - Cao, Zhiqian; Hu, Haibo; Wu, Mingzai; Tang, Kun; Jiang, Tongtong
Abstract : Planar all-solid-state rechargeable Zn–air batteries with superior energy efficiency demonstrate a novel design for compact all-solid-state rechargeable ZABs towards next-generation wearable energy storage devices with high energy density and safety. Abstract : Limited by insufficient energy density or poor safety, current state-of-the-art compact energy storage systems such as micro-supercapacitors (MSCs) and flexible lithium-ion batteries (LIBs) remain far from satisfactory for wearable applications. Herein, planar all-solid-state rechargeable Zn–air batteries (PAR-ZABs) are developed with highly active core–shell-structured Fe/Fe3 C@N-doped-carbon nanorod-clusters as bifunctional electrocatalysts deposited on interdigital carbon cloth for the air cathode, interdigital Zn-foil as the metal anode, and well-designed poly(acrylamide- co -acrylic acid) alkaline gel as an incombustible solid-state electrolyte. The presented PAR-ZABs exhibit competitive areal energy density (12.76 mW h cm −2 ) and specific energy density (832 W h kg −1 ) comparable to those of MSCs/LIBs, and higher open-circuit-voltage (1.43 V), larger specific capacity (∼736 mA h g −1 ), and better cycling stability (120 cycles/40 h at 5 mA cm −2 ) over most currently reported all-solid-state ZABs based on the conventional polyvinyl alcohol alkaline gel electrolyte. In addition, benefiting from the excellent mechanical properties of solid polymer electrolytes and the more rational planar structural design, the PAR-ZABs acquire additionally excellent flexibility, performing steadily under repeated bending deformation. More importantly, the excellent flexibility combined with the intrinsic safety of the hydrogel electrolyte endows the PAR-ZABs with outstanding wearability. Most notably, the employed in-plane electrode configuration guarantees the compact shape and good coplanar integration capability of the PAR-ZABs, enabling on-demand control of the output voltage/current with their arbitrary series/parallel connection and ensuring more compatibility to available space within microelectronics. Eventually, a wearable smart watch powered by the coplanar integrated PAR-ZAB watchband is demonstrated, showing great potential for compact wearable energy storage.